Intraoperative prevention of postoperative hypoparathyroidism - Vabalayte, Kristina; Romanchishen, Anatoly; Somova, Aleksandra (Frontiers in Endocrinology, 2023)
Objective More than 30,000 thyroid surgeries are performed annually in the Russian Federation. The surgeries are relatively safe because of the prevention methods for postoperative complications. Currently, there is no single effective method of postoperative hypoparathyroidism prevention. This complication is frequently reported and may be health and life-threatening. Aim We aimed to estimate the effectiveness of the intraoperative ICG-angiography and intrathyroid injection of Brilliant Green for the prevention of postoperative hypoparathyroidism. Material and methods One hundred and forty-three thyroidectomies were performed. Patients were divided into three groups: intraoperative angiography was used in 24 cases; Brilliant Green was injected in 58 cases to identify parathyroid glands; the visual estimation of the parathyroid preservation was used in 61 cases. Calcium level was measured in all patients before and after surgery. Results Calcium level in the serum before and after surgery was 2.37±0.14 and 2.27±0.17 in Group 1, 2.38±0.16 and 2.21±0.16 in Group 2, and 2.39±0.17 and 2.18±0.19 in Group 3. Postoperative hypocalcemia was more prominent in the group with the visually estimated PTG than in the two other groups. The differences in postoperative calcium levels in Groups 1 and 3 were statistically different. Pre- and postoperative Parathormone levels were 6.2±0.4 in Group 1, 5.6±0.57 in Group 2, and 3.5±0.32 in Group 3. Postoperative levels significantly differed in Groups 1 and 3 (p<0.01) and in Groups 2 and 3 (p<0.05). Conclusions ICG-angiography and intrathyroid injection of the Brilliant Green are safe methods of identification and sparing of the parathyroid glands. The severity of hypocalcemia and hypoparathormonemia in Group 3 shows the necessity of finding new methods in endocrine surgery to improve patient outcomes.